Comparative effectiveness of aggressive versus nonaggressive treatment among men with early‐stage prostate cancer and differing comorbid disease burdens at diagnosis. Issue 16 (13th May 2014) - Daskivich, Timothy J.; Lai, Julie; Dick, Andrew W.; Setodji, Claude M.; Hanley, Janet M.; Litwin, Mark S.; Saigal, Christopher; ,
Abstract : BACKGROUND: This study sought to compare the effectiveness of aggressive versus nonaggressive treatment in reducing cancer‐specific mortality for older men with early‐stage prostate cancer across differing comorbid disease burdens at diagnosis. METHODS: In total, the authors sampled 140, 553 men aged ≥66 years with early‐stage prostate cancer who were diagnosed between 1991 and 2007 from the Surveillance, Epidemiology, and End Results‐Medicare database. Propensity‐adjusted competing‐risks regression analysis was used to compare the risk of cancer‐specific mortality between men who received aggressive versus nonaggressive treatment among comorbidity subgroups. RESULTS: In propensity‐adjusted competing‐risks regression analysis, aggressive treatment was associated with a significantly lower risk of cancer‐specific mortality among men who had Charlson scores of 0, 1, and 2 but not among men who had Charlson scores ≥3 (subhazard ratio, 0.85; 95% confidence interval, 0.62‐1.18). The absolute reduction in 15‐year cancer‐specific mortality between men who received aggressive versus nonaggressive treatment was 6.1%, 4.3%, 3.9%, and 0.9% for men with Charlson scores of 0, 1, 2, and ≥3, respectively. Among men who had well‐differentiated and moderately‐differentiated tumors, aggressive treatment again was associated with a lower risk of cancer‐specific mortality for those who had Charlson scores of 0, 1, and 2 but not for those who had Charlson scores ≥3 (subhazard ratio, 1.14; 95% confidence interval, 0.70‐1.89). The absolute reduction in 15‐year cancer‐specific mortality between men who received aggressive versus nonaggressive treatment was 3.8%, 3%, 1.9%, and −0.5% for men with Charlson scores of 0, 1, 2, and ≥3, respectively. CONCLUSIONS: The cancer‐specific survival benefit from aggressive treatment for early‐stage prostate cancer diminishes with increasing comorbidity at diagnosis. Men with Charlson scores ≥3 garner no survival benefit from aggressive treatment. Cancer 2014;120:2432–2439. © 2014 American Cancer Society . Abstract : The cancer‐specific survival benefit associated with aggressive treatment for early‐stage prostate cancer diminishes with increasing comorbidity at diagnosis. Men with Charlson scores of 3 or greater garner no survival benefit from aggressive treatment.